2006
DOI: 10.1124/jpet.106.103713
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Glyceryl Trinitrate by Rat Hepatic Microsomal GlutathioneS-Transferase 1

Abstract: Although the biotransformation of organic nitrates by the cytosolic glutathione S-transferases (GSTs) is well known, the relative contribution of the microsomal GST (MGST1) to nitrate biotransformation has not been described. We therefore compared the denitration of glyceryl trinitrate (GTN) by purified rat liver MGST1 and cytosolic GSTs. Both MGST1 and cytosolic GSTs catalyzed the denitration of GTN, but the activity of MGST1 toward GTN was 2-to 3-fold higher. To mimic oxidative/nitrosative stress in vitro, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…2 and 3). These findings suggest that nitroglycerin is bioactivated and exerts physiological effects through its metabolism at higher doses, which is consistent with findings of multiple enzyme-dependent ways to activate nitroglycerin (6,8,9). Nevertheless, taken together, our experiments demonstrated that such pathways dependent on metabolism are not likely to be the major routes operating in vivo at therapeutic nitroglycerin doses (1-10 nM).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…2 and 3). These findings suggest that nitroglycerin is bioactivated and exerts physiological effects through its metabolism at higher doses, which is consistent with findings of multiple enzyme-dependent ways to activate nitroglycerin (6,8,9). Nevertheless, taken together, our experiments demonstrated that such pathways dependent on metabolism are not likely to be the major routes operating in vivo at therapeutic nitroglycerin doses (1-10 nM).…”
Section: Discussionsupporting
confidence: 79%
“…Since then, intense research has led to extensive and well documented literature regarding nitroglycerin's physiological effects (2)(3)(4) and the identity of its derived metabolites in cells, tissues, laboratory animals, and humans (5,6). Although much of nitroglycerin's pharmacology is known, the mechanisms through which nitroglycerin acts on the endothelium and the heart as well as the enzymatic pathways leading to its bioactivation are still controversial and under intense investigation.…”
mentioning
confidence: 99%
See 3 more Smart Citations